2021
DOI: 10.1002/cbic.202000746
|View full text |Cite
|
Sign up to set email alerts
|

An Economical High‐Throughput “FP‐Tag” Assay for Screening Glycosyltransferase Inhibitors**

Abstract: O-GlcNAc transferase (OGT) is involved in many cellular processes, and selective OGT inhibitors are valuable tools to investigate O-GlcNAcylation functions, and could potentially lead to therapeutics. However, high-throughput OGT assays that are suitable for large-scale HTS and can identify inhibitors targeting both acceptor, donor sites, and allosteric binding-sites are still lacking. Here, we report the development of a highthroughput "FP-Tag" OGT assay with bovine serum albumin (BSA) as a low-cost and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…As a marine natural product research group, we have a long-term interest to find bioactive molecules from the marine environment, and indeed we have previously successfully identified several potent inhibitors from marine natural product libraries with FP-based assays [31] , [32] . Therefore, we performed a pilot HTS with a small marine natural product library (about 300 compounds) at 10 µM ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…As a marine natural product research group, we have a long-term interest to find bioactive molecules from the marine environment, and indeed we have previously successfully identified several potent inhibitors from marine natural product libraries with FP-based assays [31] , [32] . Therefore, we performed a pilot HTS with a small marine natural product library (about 300 compounds) at 10 µM ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…As a marine natural product research group, we have a long-term interest to find bioactive molecules from the marine environment, and indeed we have previously successfully identified several potent inhibitors from marine natural product libraries with FP-based assays [31-32] . Therefore, we performed a pilot HTS with a small marine natural product library (about 300 compounds) at 10 µM (Figure 7A).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this method, 2-methyleurotinone was identified as a low-μM OGT inhibitor. The BSA-based "FP-Tag" will be applicable to other types of glycosyltransferases 49 . In 2020, Seebald et al reported the synthesis and application of fluorescent nucleoside analogues as the foundation for directed approaches for competitive binding analyses.…”
Section: Fluorescently Modified Glycosyl Donors and Acceptorsmentioning
confidence: 99%